PEMAHAMAN TENTANG LINGKUNGAN BERKELANJUTAN - Rahayu Effendi; Hana Salsabila; Abdul Malik (architecture department, Engineering faculty, Universitas Diponegoro, 2018)
The rapid rise of population, the increasing need of human beings and the development of science and technology causes the environment to be sacrificed to meet the needs of human life. Therefore, the importance of realizing a sustainable, principled environment in maintaining health and addressing ecological and ecosystem balance issues as an effort to ensure the survival of future generations. This paper discusses the sustainable environment, covering the basics of environmental sustainability that is ecology and ecosystems and accompanied by case studies aimed at providing a clearer picture of how the environment is sustainable. The purpose of this paper is to provide understanding to the community what and how the importance of environmental sustainability is so that later can be applied in real terms to create a healthy environment and ensure sustainability of the present and future